Toxicité Aigüe Et Effets Des Extraits Des Feuilles De Cogniauxia Podolaena Bail. (Cucurbitaceae) Sur L’excrétion Fécale Et La Motilité Intestinale - Elion Itou RDG; Etou Ossibi AW; Morabandza CJ; Kiessé D.S.; Mayela Nkouka S.H.J; Abena AA (European Scientific Journal, ESJ, 2017)
This work aims to estimate acute toxicity and to evaluate the effects of the aqueous and hydroethanolic extracts of leaves (Cucurbitaceae) of Cogniauxia podolaena on the fecal excretion and the intestinal motility. The estimation of the acute toxicity was made by oral administration of the aqueous and hydroéthanolique extracts in the doses of 2000 and 500 mg/kg in mice in order to determine the lethal dose 50 (LD50) and the experimental doses. No sign of toxicity was observed with the hydroethanolic extract in mice. The aqueous extract of Cogniauxia podolaena is slightly toxic with a lethal dose estimated at the dose of 3167 mg/kg. For that, the doses of 300 and 600 mg/kg were retained for experiment. The effect of the both extracts at 300 and 600 mg/kg was evaluated on the fecal excretion directly on the normal animals and on the intestinal motility according to the method of coal. The hydroethanolic extract (300 and 600 mg/kg) increased the fecal excretion in rats. Aqueous extract (300 and 600 mg/kg) did not present effects. The both extracts in doses used does decrease the speed of intestinal evacuation. The effect of hydroethanolic extract is low at the dose of 600 mg/kg. These results do not seem to confirm the traditional use of this plant in the constipation coverage.